The contribution of nonrigid motion and shape information to object perception in pigeons and humans - Nankoo, Jean-Francois; Madan, Christopher R.; Sawalha, Jeffrey; Wylie, Douglas R.; Friedman, Alinda; Spetch, Marcia L.; Vuong, Quoc C. (Association for Research in Vision and Ophthalmology, 2017)
The ability to perceive and recognize objects is essential to many animals, including humans. Until recently, models of object recognition have primarily focused on static cues, such as shape, but more recent research is beginning to show that motion plays an important role in object perception. Most studies have focused on rigid motion, a type of motion most often associated with inanimate objects. In contrast, nonrigid motion is often associated with biological motion and is therefore ecologically important to visually dependent animals. In this study, we examined the relative contribution of nonrigid motion and shape to object perception in humans and pigeons, two species that rely extensively on vision. Using a parametric morphing technique to systematically vary nonrigid motion and three-dimensional shape information, we found that both humans and pigeons were able to rely solely on either shape or nonrigid motion information to identify complex objects when one of the two cues was degraded. Humans and pigeons also showed similar 80% accuracy thresholds when the information from both shape and motion cues were degraded. We argue that the use of nonrigid motion for object perception is evolutionarily important and should be considered in general theories of vision at least with respect to visually sophisticated animals.